A Study On The Management Approaches Adopted By Individuals With Osteoarthritis Knee In Karad: Life Sciences-Physiotherapy for Better Medical Therapy - Minal .B. Masekar; Dr. Smita Patil; Dr. Chandrakant Patil; Dr. Khushboo Chotai (International Journal of Life Science and Pharma Research, 2022)
Osteoarthritis (OA) is a degenerative condition of the joints characterised by focal loss of articular cartilage along with sclerosis of subchondral bone and formation of osteophytes. The purpose of this study was to determine the various management approaches adopted by the people suffering from knee osteoarthritis. As this condition affects a large population the methods use to deal with the symptoms differ which are described in this study highlighting the preference of a physiotherapist by the patients. The study was carried out in Krishna Hospital, Karad with the sample size of 60 using purposive sampling method, a cross sectional study was performed using a descriptive study design. Individuals with Osteoarthritis of knee are included based on the inclusion and exclusion criteria. The data collected was analysed qualitatively which resulted in 65% participants who approached General practitioner (GP) as initial approach, with only 6% approaching a physiotherapist. 81% used heat therapy as a measure to manage their symptoms while only 30% used exercises as a modality. The primary finding was that there is no clear pathway for management of Osteoarthritis of knee in Karad. Majority opted for General-Practitioner as their initial approach. Physiotherapists were preferred only by a few, not many were seen utilising exercise modality. Since there is a vast difference in treatments by variety of individuals, this study will thus help in determining the various approaches for knee osteoarthritis and establishing a definitive and effective protocol for the management of the patients symptoms.